Comparative study on 4G/LTE cryptographic algorithms based on different factors - Ghanim, Alyaa; Alshaikhli, Imad Fakhri Taha (IJCST, 2014)
Recently, (LTE) Long Term Evolution appeared as a robust technology to meet (4G) Fourth Generation cellular networks requirements. Apparently, there are three sets of cryptographic algorithms that work on LTE technology and each set based on core algorithm. Therefore, in this paper we are focusing on reviewing the three sets of the LTE cryptographic algorithms and their core algorithms and then comparing them based on different factors in order to understand their cons and pros and provide valuable information about LTE security.